Geopolitics of Energy in the Kastellorizo-Cyprus Middle East Complex: Based on the Existing Geophysical and Geological Indications of Hydrocarbon Deposits - Ioannis Mazis; Georgios Sgouros (Regional Science Inquiry, 2010)
The geophysical and geological submarine features (pockmarks, gas chimneys, salt domes, etc.),identified by multi-beam echo sounders and sidescan sonars ,seismic surveys in the region South, South-west and South-east of Cyprus, as well as the corresponding international interest of investors, especially in the marine region of the Levantine Basin, lead to the conclusion that, from a geopolitical standpoint, Greece must be urged to accelerate the consolidation of its sovereign rights and understand anew and in practical terms, that “Cyprus is not far away, not at all actually”. With respect to Kastellorizo and the submarine area of its EEZ, we note that detailed geophysical and bathymetric surveys have confirmed the fact that the region of the submarine Anaximander Mountains presents active mud volcanoes that are linked to the presence of gas hydrates. Samples of gas hydrates were collected by means of indicative samplings in mud volcanoes thoroughly mapped in sub-seabed layers that do not exceed 1.5 m. These “ice-crystal” like features will probably have a significant socioeconomic impact in the near feature as an energy resource. New mud volcanoes were also discovered (“Athens” and “Thessaloniki”). Gas hydrates were found in samplings conducted in the “Thessaloniki” M.V. According to preliminary assessments, the total capacity of the mud volcanoes of the Anaximander mountains complex is estimated between 2.56-6.40 c. km. Geopolitics of Energy, Cyprus, Israel, Levantine, multi-beam echo sounders, side scan sonars, pockmarks, gas chimneys, salt domes, Exclusive Economic Zone/EEZ.